Memory of space and place: tourism as factor of life or death of cities - Saraiva, A. (2018)
The memory of space and place are reflected in our experience. Tourism is currently an uncontrollable mobility factor - whether human, identities, cultures, meanings, information, finance and objects - that cause changes and changes in space and place. Gaston Bachelard (1964), Edward Casey (2000) as philosophers and phenomenologist have also traced this powerful connection between memory and place. The work of Jane Jacobs (2001) is essential in this reading. Yi-Fu Tuan (2001) had a different approach and suggests that memorable architecture should strengthen our memories, enhance the self, and provide layers of meaning to a space. The purpose of this article is to understanding the spatial relationships and tensions between them, and how tourism can be a factor of life or death in the cities. How dynamics allows us to gain important insights into the processes that shape the spaces and places, without losing the original identity. This article will treat conceptual aspects that relate to the theme, bringing to this context the concepts of space and place.